PENGARUH RETURN OF ASSET, RETURN OF EQUITY, NET PROFIT MARGIN, DAN EARNINGS PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2009-2012 - Rakidewo, Pion Seto; Champaca, Mychelia (Jurnal Ilmiah Mahasiswa FEB, 2014)
From some of the facts, the performance of manufacturing firms in 2014 is predicted  to decline that led to investor uncertainty in determining investment decisions. Therefore,  investors need to measure the success of the company in investment activity through the  analysis of the profitability ratio, which is expected to be used to predict the stock price with  good manufacturing company. The purpose of research to determine the effect Return on  Assets (ROA), Return on Equity ( ROE ), Net Profit Margin (NPM) and Earning Per Share  (EPS) simultaneously significant effect on stock prices and to determine the effect of Return  On Equity (ROE), Return On Assets (ROA), Net Profit Margin ( NPM ) and Earning Per  Share (EPS) is partially significant effect on stock prices.Kata kunci : Return on Assets, Return on Equity, Net Profit Margin, Earning Per Share, dan Harga Saham.